Structural plasticity of BCL-2 family proteins and its functional implication in apoptosis - Choi, Minjoo (2018)
Dysregulated apoptosis has been implicated in the development of several diseases including cancer and neurodegenerative diseases. Bcl-2 family proteins regulate mitochondrial apoptosis through homo- and hetero-dimerization between pro- and anti-apoptotic Bcl-2 proteins. The first part of this study has been devoted to address the structural transition of Bcl-xL in forming domain-swapped dimer in the presence of n-octyl-β-D-Maltoside detergent. We postulated that this structural plasticity of Bcl-xL might play a regulatory role in the modulation of mitochondrial calcium homeostasis. In the second part of this study, we focused on the molecular interaction between Bcl-xL and Voltage-Dependent Anion Channel (VDAC). While VDAC has been reported to interact with Bcl-xL to regulate mitochondrial calcium homeostasis, detailed molecular basis of the interaction between the two molecules remains elusive. Hence, we aim to provide structural insights into the interaction of Bcl-xL with VDAC N-terminal peptides using NMR spectroscopy.